Basic researchThe effects of palmvitee on d-aminolevulinic acid-induced hyperbilirubinaemia in suckling rats - Kamisah, Yusof; Norhayati, Mohd Y.; Zakri, Bustaman; Asmadi, Ahmad Y. (Archives of Medical Science, 2009)
Introduction: Our previous study has shown that maternal administration of palmvitee reduced plasma total bilirubin in hyperbilirubinaemic rat neonates. Therefore, this study was conducted to investigate the effects of palmvitee on hyperbilirubinaemia induced by d-aminolevulinic acid (ALA) in rat neonates. Material and methods: Sixty Wistar rat neonates were divided into two groups. One group was injected 30 mg palmvitee/kg body weight intraperitoneally once daily starting on day 1 through day 14 postnatal, while the other group was given olive oil (control). At day 14 postnatal, half of the sucklings from each group were induced with hyperbilirubinaemia, while the rest were given vehicle. Twenty-four hours after the induction, the neonates were sacrificed. Plasma total bilirubin, hepatic thiobarbituric acid reactive substance (TBARS), UDP-glucuronyltransferase (UGT) activity and vitamin E content were determined. Results: ALA administration increased plasma total bilirubin, but palmvitee pre-treatment prevented this increase (0.16 ±0.03 vs. 0.32 ±0.01 mg/dl). ALA administration did not affect the hepatic UGT activity, but in the neonates given palmvitee, it was reduced significantly. ALA also did not influence hepatic TBARS content. However, the TBARS was lower in the palmvitee-treated groups. The neonatal hepatic vitamin E content was increased following palmvitee pre-treatment. Conclusions: Palmvitee administration confers protective effect against hyperbilirubinaemia. However, this administration could lead to a decreased hepatic glucuronidation activity in the hyperbilirubinaemic rat neonates induced by ALA.